One World, Many Knowledges Regional experiences and cross-regional links in higher education - Vale, Peter C. J.; Halvorsen, Tor; Project Muse; Project Muse. (Project Muse, 2016)
Various forms of academic co-operation criss-cross the modern university system in a bewildering number of ways, from the open exchange of ideas and knowledge, to the sharing of research results, and frank discussions about research challenges. Embedded in these scholarly networks is the question of whether a 'global template' for the management of both higher education and national research organisations is necessary, and if so, must institutions slavishly follow the high-flown language of the global 'knowledge society' or risk falling behind in the ubiquitous university ranking system? Or are there alternatives that can achieve a better, 'more ethically inclined, world? Basing their observations on their own experiences, an interesting mix of seasoned scholars and new voices from southern Africa and the Nordic region offer critical perspectives on issues of inter- and cross-regional academic co-operation. Several of the chapters also touch on the evolution of the higher education sector in the two regions. An absorbing and intelligent study, this book will be invaluable for anyone interested in the strategies scholars are using to adapt to the interconnectedness of the modern world. It offers fresh insights into how academics are attempting to protect the spaces in which they can freely and openly debate the challenges they face, while aiming to transform higher education, and foster scholarly collaboration. The Southern African-Nordic Centre (SANORD) is a partnership of higher education institutions from Denmark, Finland, Iceland, Norway, Sweden, Botswana, Namibia, Malawi, South Africa, Zambia and Zimbabwe. SANORD's primary aim is to promote multilateral research co-operation on matters of importance to the development of both regions. Our activities are based on the values of democracy, equity, and mutually beneficial academic engagement.
Introduction : why this book, and what it's about / Tor Halvorsen and Peter Vale -- part I. Background -- 1. The Southern African-Nordic Centre : from conception to realization / Stanley G.M. Ridge -- 2. Drivers and challenges in the internationalisation of higher education and research : the case of the Southern African-Nordic Centre / Anne S{ostok}rensen -- part II. Dilemmas of change -- 3. Changes in higher education policy and the Nordic model / Risto Rinne -- 4. University transformation : a crisis for the social sciences and the humanities / Tor Halvorsen -- 5. Redressing apartheid's legacy of social exclusion : social equity, redress and admission to higher education in South Africa / Saleem Badat -- part III. Inclusion and exclusion -- 6. The struggle, global challenges and international strategies in the University of Fort Hare's music department / Bernhard Bleibinger -- 7. The migration of African students to South Africa : motivations, integration and prospects for return / Gabriel Tati -- 8. The experiences of deaf students at a South African university / Lucas Magongwa -- 9. Tradition and modernity : the inclusion and exclusion of traditional voices and other actors in archaeological heritage management in Mozambique and Zimbabwe / Albino Jopela, Ancila Nhamo and Seke Katsamudanga -- 10. Steering from a distance : improving access to higher education in South Africa via the funding formula / Pieter le Roux and Mignonne Breier -- part IV. Critical perspectives -- 11. Cultural heritage and social context : research and management in Mozambique / Anne Bang and Tore S{aelig}tersdal -- 12. Academic co-operation in a bipolar world : where does SANORD fit in? / Tor Halvorsen -- 13. Whatever happened to imagination? / Peter Vale.
"First published 2012 by the Southern African-Nordic Centre"--Title page verso.
Issued as part of book collections on Project MUSE.
Includes bibliographical references.
Description based on print version record.
Keywords: Education, Higher -- Administration -- Cross-cultural studies; Higher education and state -- Cross-cultural studies; Education, Higher -- South Africa; Education, Higher -- Africa; Electronic books; Electronic books